TEACHER EDUCATION FOR CHILDHOOD EDUCATION: INTEGRATION BETWEEN REQUIRED EDUCATION AND CARE FOR EDUCATIONAL PRAXIS EMANCIPATORY - Mantovani Leite, Sandra Regina [UNESP]; Carvalho, Alonso Bezerra de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
This study aims to present the importance of teacher training for early childhood education, enhancing the integration of education and care as a primary function in working with small children, as also intends to reflect on the importance of teacher performance in processes growing dialogue with the child. Though we live in a modern society with legal changes that began to consider the child as a subject of rights is necessary to think about the specifics of teaching to make this special moment of childhood. It is considered that children who are part of the Early Childhood Education Institutions are an important stage of their lives when they depend on adults intensely, being necessary to assist them in activities that cannot perform alone, meeting them in their basic security needs, nutrition, hygiene, and health and affection for both the facilitator's role is essential. So the challenge that is established when the intention is to think the training of Childhood Teachers is to present the specifics of teaching in Early Childhood Education, as well as issues surrounding the valuation of this professional seeking a committed relationship of dialogue with the full development of the child.
Keywords: Teacher training; Child; Dialogic relationship